Coronary Heart Disease Risk and Associated Risk Factor Among Workers at PT.X in 2023 - Jeanita Haldy; L. Meily Kurniawidjaja (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Coronary heart disease is also a major cause of death and permanent disability among workers. In Indonesia, the estimated loss due to decreased productivity and treatment costs for CHD is 6.8% of GDP per year. The risk of CHD in industry is increased due to stress from long working hours, shift work affecting work, eating, and sleeping patterns. Objective: To evaluate the risk of CHD among workers at PT. X, an oil and gas company, and to describe the frequency distribution of CHD risk factors Method: The research design is descriptive analytics with a cross-sectional design. Sample data was collected from annual health examination data at PT. X in 2023. Framingham risk score (FRS) used to predict the incidence rate of CHD in the next 10 years. Result: The data of PT. X indicates that man employees comprise 76.2%, age <40 years old 44.9%, 8.8% of employees have hypertension, 2.6% diabetes, and 62.1% obese. The results of CHD prediction risk calculations using Framingham are 0.4% of workers at high risk, 15.9% at intermediate risk. Risk factor of CHD found gender (pvalue = 0,000 ; OR 18,6), age (pvalue = 0,000; OR 54,3), SBP (pvalue = 0,002; OR 3,2), TC (pvalue = 0,032; OR 2,1), HDL (pvalue = 0,017; OR 0,4), fasting blood sugar (pvalue = 0,000; OR 6,5), smoking habits (pvalue = 0,000; OR 4,8), and BMI (pvalue = 0,013; OR 4,2). Conclusion: The results of predicting the risk of coronary heart disease over the next 10 years using Framingham among PT.X workers indicate that 0.4% of workers have a high risk and 15.9% have a intermediate risk. Gender, age, systolic blood pressure, total cholesterol, HDL, fasting blood sugar, smoking habits, and body mass index (BMI) are significantly associated with the risk of coronary heart disease.